2010
DOI: 10.1016/j.jasms.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mapping N-terminus phosphorylation sites and quantitation by stable isotope dimethyl labeling

Abstract: We have previously coupled stable isotope dimethyl labeling with IMAC enrichment for quantifying the extent of protein phosphorylation in vivo. The enhanced a 1 signal of dimethylated peptides served as a unique mass tag for unequivocal identification of the N-terminal amino acids. In this study, we demonstrate that the a 1 ion could further assist in mapping the precise phosphorylation site near the N-terminal region and allow the determination of the exact site and level of phosphorylation in one step by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Wu et al reported that the a 1 signal was suppressed for precursor ions with phosphorylated Ser/Thr N-termini (N-p*Ser/Thr) but no suppression was observed for the precursor ion with phosphorylated Tyr N-terminus [36]. Although somehow negative, this provides a useful hint for mapping phosphorylation sites at the N-termini [106]. Despite diverse usefulness, a 1 ion is not detectable for ion trap instruments due to the '1/3 rule', which also occurs for other tandem mass tags like iTRAQ.…”
Section: Applications Beyond Quantitative Analysismentioning
confidence: 99%
“…Wu et al reported that the a 1 signal was suppressed for precursor ions with phosphorylated Ser/Thr N-termini (N-p*Ser/Thr) but no suppression was observed for the precursor ion with phosphorylated Tyr N-terminus [36]. Although somehow negative, this provides a useful hint for mapping phosphorylation sites at the N-termini [106]. Despite diverse usefulness, a 1 ion is not detectable for ion trap instruments due to the '1/3 rule', which also occurs for other tandem mass tags like iTRAQ.…”
Section: Applications Beyond Quantitative Analysismentioning
confidence: 99%
“…Quantitative proteome analysis by shotgun approach coupled with stable isotope dimethyl labeling has been used in identifying candidate biomarkers or target factors in different types of samples on account of the fact that this approach can detect differentially released proteins at relatively low abundance [28][29][30][31]. In this study, we conducted a comparative proteomics investigation of urine between HCC patients and control group by a bottom-up shotgun proteomic approach.…”
Section: Protein Expression Levels Analyzed By Nanolc-ms/msmentioning
confidence: 99%
“…In this study we aim to conduct the comparative and quantitative proteome analysis between RCC and their nearby normal portion of the same tissue by means of gel-free shotgun proteomic approach coupled with stable isotope dimethyl labeling and nanoLC-MS/MS [26][27][28][29]. The differentially expressed proteins identified by the quantitative approach will be employed to delineate the biosignaling pathways involved in the tumorigenesis of RCC.…”
Section: Introductionmentioning
confidence: 99%